A Theory of Fields (Excerpt) - Neil Fligstein; Doug Mcadam (Journal of Economic Sociology, 2022)
The central goal of this book is to explicate an integrated theory that explains how stability and change are achieved by social actors in circumscribed social arenas. The theory rests on a view that sees strategic action fields, which can be defined as mesolevel social orders, as the basic structural building blocks of modern political/organizational life in the economy, civil society, and the state. In constructing a new perspective, the authors draw upon the rich body of integrative scholarship produced by economic sociologists, institutional theorists in both sociology and political science, and social movement scholars. The Journal of Economic Sociology is pleased to publish the first chapter, “The Gist of It.” In this chapter, the authors sketch the basic features of this perspective in some detail, differentiating the new elements from the old, including Bourdieu, Giddens, institutional theory, network analysis, and social movement theory.